Counsellor Education as part of Inclusive Liberal Education - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2007)
Perhaps one of the most effective ways for counsellor educators to respond to contemporary challenges both within and outside of the academy is to position themselves and their work more centrally with respect to contemporary debates surrounding both higher education and the delivery of human services. By adopting, and identifying with, the curriculum content and scholarly goals of a relevant and inclusive liberal education, counsellor eduction might assist both counsellor educators and student counsellors to act as bona fide scholar-practitioners in ways likely to benefit the contemporary academy and society at large.